The safety and effectiveness of a long‐acting transdermal fentanyl solution compared with oxymorphone for the control of postoperative pain in dogs: a randomized, multicentered clinical study. Issue 4 (18th December 2013) - Martinez, S. A.; Wilson, M. G.; Linton, D. D.; Newbound, G. C.; Freise, K. J.; Lin, T.‐L.; Clark, T. P.
<x xml:space="preserve">Abstract</x> A prospective, double‐blinded, positive‐controlled, multicenter, noninferiority study was conducted to evaluate the safety and effectiveness of transdermal fentanyl solution (TFS) compared with oxymorphone for the control of postoperative pain in dogs. Five hundred and two (502) client‐owned dogs were assigned to a single dose of TFS (2.7 mg/kg) applied 2–4 h prior to surgery or oxymorphone hydrochloride (0.22 mg/kg) administered subcutaneously 2–4 h prior to surgery and q6h through 90 h. Pain was evaluated over 4 days by blinded observers using a modified Glasgow composite pain scale, and the a priori criteria for treatment failure was a pain score ≥8 or adverse event necessitating withdrawal. Four TFS‐ and eight oxymorphone‐treated dogs were withdrawn due to lack of pain control. Eighteen oxymorphone‐treated, but no TFS‐treated dogs were withdrawn due to severe adverse events. The one‐sided upper 95% confidence interval of the difference between TFS and oxymorphone treatment failure rates was −5.3%. Adverse events associated with oxymorphone were greater in number and severity compared with TFS. It was concluded that a single administration of TFS was safe and noninferior to repeated injections of oxymorphone for the control of postoperative pain over 4 days at the dose rates of both formulations used in this study.